Impact of Austria's 2009 trans fatty acids regulation on all-cause, cardiovascular and coronary heart disease mortality - Grabovac, Igor (Eur J Public Health, 2018)
BACKGROUND: Unhealthy diet, especially consumption of trans fatty acids (TFAs), is a known risk factor for cardiovascular disease (CVD), a leading cause of death in Austria. In 2009, Austria introduced a law regulating the content of TFAs in foods. The aim of this study was to assess the impact of the TFA regulation on CVD-related outcomes. METHODS: The study evaluated the TFA regulation as an intervention in a natural experiment. Two study periods were assessed: pre-intervention (1995–2009) and post-intervention (2010–14). The study compared the age-standardized death rates per 100 000 population for CVD outcomes with those of a ‘synthetic’ international comparator population, created from data of OECD countries where TFA regulation has not been implemented, but where the population is otherwise comparable. RESULTS: There was a continuous decrease in CVD-related mortality throughout the study period in both the synthetic international comparator population, as well as in the adult Austrian population, with no significant change in this trend observed as an effect of TFA regulation. CONCLUSIONS: Whilst the results are counterintuitive, given the established link between TFA consumption and an increased risk of CVD, there are many possible explanations: high prevalence of tobacco smoking, changes in TFA content in foods due to international guidance as opposed to formal regulation and a beneficial impact of TFA regulation on sub-groups of the population that might not be detected with nationally aggregated data. However, reduction in TFAs should still be considered an important part of risk factor reduction for CVD and other non-communicable diseases.